Traveling Wave Solutions in a Chemotaxis Model with Two Chemoattractants (Journal of Nonlinear Modeling and Analysis, 2024)
In this work, we investigate the existence and non-existence oftraveling wave solutions for a chemotaxis model with two chemoattractants.To prove our main results, we apply the dynamical systems theory by constructing a positively invariant set in the four-dimensional space. Particularly,we analyze the monotonicity of traveling wave solutions.
Keywords: Chemotaxis model; traveling wave solutions; dynamical systems theory.